A Colourachal-Cutaneous Fistula: A Report of an Unusual Case. (31st January 2013) - Gargouri, Mohamed Mourad; Boulma, Rami; Sallemi, Ahmed; Chlif, Mohamed; Fitouri, Zouhaier; Kallel, Yosri; Nouira, Yassine
Abstract : Urachal anomalies are rare affections due to incomplete closure of urachus during foetal period. Colo-urachal-cutaneous fistula is an uncommon complication of urachal anomalies. Only three cases have been reported so far in the literature. Herein, we report a new case in a 51-year-old patient presenting with umbilical feculent discharge lasting for 4 weeks. Diagnosis was made by computed tomography. After en bloc total surgical excision followup was uneventful.